Analysis of Coal Spontaneous Combustion by Thermodynamic Methods. Issue 13 (3rd October 2021) - Xi, Zhilin; Shan, Ze; Li, Meitong; Wang, Xiaodong
ABSTRACT: In order to better determine the spontaneous combustion tendency of coal, two types of heating rate methods, namely, single and multi-scan methods, commonly used in the field of spontaneous coal combustion are summarized based on a thermal analysis kinetics method. The single scanning rate method mainly included the Coats–Redfern, Achar, universal equation, MacCallum–Tanner, Madhusudanan–Krishnan–Ninan, and non-isothermal thermogravimetric and differential scanning calorimetric methods. The multi-scan rate method mainly included the Flynn–Wall–Ozawa, Kissinger–Akahira–Sunose, Starink, and Friedman methods. For each of these methods, their respective theoretical basis, advantages, and disadvantages were described. In addition, the Popesc and Malek methods were used to determine the optimal reaction kinetic model. In view of the compensation effect, the invariable activation energy E inv and the pre-exponential factor ln Ainv at different heating rates were determined. For each method, the oxygen weight gain stage of Shaanxi bituminous coal was selected as an example interpretation.